Crystal structure of the cell division protein FtsA from Thermotoga maritima - van den Ent, Fusinita (Oxford University Press, 2000)
Bacterial cell division requires formation of a septal ring. A key step in septum formation is polymerization of FtsZ. FtsA directly interacts with FtsZ and probably targets other proteins to the septum. We have solved the crystal structure of FtsA from Thermotoga maritima in the apo and ATP-bound form. FtsA consists of two domains with the nucleotide-binding site in the interdomain cleft. Both domains have a common core that is also found in the actin family of proteins. Structurally, FtsA is most homologous to actin and heat-shock cognate protein (Hsc70). An important difference between FtsA and the actin family of proteins is the insertion of a subdomain in FtsA. Movement of this subdomain partially encloses a groove, which could bind the C-terminus of FtsZ. FtsZ is the bacterial homologue of tubulin, and the FtsZ ring is functionally similar to the contractile ring in dividing eukaryotic cells. Elucidation of the crystal structure of FtsA shows that another bacterial protein involved in cytokinesis is structurally related to a eukaryotic cytoskeletal protein involved in cytokinesis.